ANALISIS PENGARUH CURRENT RATIO, TOTAL ASSETS TURN OVER, DEBT TO ASSET RATIO DAN NET PROFIT MARGIN TERHADAP PERUBAHAN LABA - Atik; Siti Muntahanah (FEB UNWIKU PURWOKERTO, 2020)
This study aims to analyze the effect of the current ratio, total asset turnover, debt to assets ratio, and net profit margin on changes in earnings. Company size. This research was conducted in all trading companies listed on the Indonesia Stock Exchange (BEI) during the research period 2013-2015. The sample in this study were 52 trading companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2015. The sampling technique used the purposive sampling method. The analytical tool used in this study using multiple regression analysis using the SPSS application. Partial test analysis (t test) which is used to see the effect of independent variables (Current Ratio, Total Assets Turn Over, Debt to Assets Ratio and Net Profit Margin) has a significant effect on the dependent variable. The first hypothesis which states that the Latest Ratio has a significant effect on changes in earnings in trading companies is accepted, the second hypothesis related to Total Assets Turn Over has a significant effect on changes in earnings in trading companies listed on the Indonesia Stock Exchange for the period 2013 - 2015 is accepted. The hypothesis which states that the Debt to Total Assets Ratio has a significant positive effect on changes in earnings in trading companies listed on the Indonesia Stock Exchange for the period 2013 - 2015. The fourth hypothesis states that Net Profit Margin has a significant positive effect on changes in earnings in trading companies listed on the Stock Exchange. Indonesia for the period 2013 - 2015 was accepted